High-fidelity 3D models of human cadavers and their organs with the use of handheld scanner–Alternative method in medical education and clinical practice - Michalik, Weronika; Szczepanik, Magdalena; Biel, Konrad; Mordarski, Michał; Bak, Kacper; Fryzlewicz, Kamila; Jaszewski, Karol; Maciaszek, Szymon; Pierzchała, Monika; Arshad, Areej; Rams, Daniel; Walocha, Jerzy; et al. (Frontiers in Medicine, 2025)
BackgroundTraditional cadaveric dissection is considered the gold standard in anatomical education; however, its accessibility is limited by ethical, logistical, and financial constraints. Recent advancements in three-dimensional (3D) scanning technologies provide an alternative approach that enhances anatomical visualization while preserving the fidelity of real human specimens.AimThis study aimed to create digitized 3D models of dissected human cadaveric specimens using a handheld structured-light scanner, thus providing a sustainable and accessible resource for educational and clinical applications.MethodsEight human cadaveric specimens were dissected and scanned using the Artec 3D Spider handheld scanner. The obtained scans were processed in Artec Studio 17 Professional and further processed in Blender software. Finalized 3D models were exported in.MP4 format and paired with two-dimensional (2D) images for enhanced anatomical understanding.ResultsA total of 12 anatomical 3D models were successfully created, capturing detailed anatomical landmarks with a resolution of 0.1 mm and an accuracy of 0.05 mm. The models encompassed key anatomical regions or organs, including the brain, skull, face, neck, thorax, heart, abdomen, pelvis, and lower limb. The combination of 3D models alongside 2D images allowed for interactive and immersive learning, as well as improving spatial comprehension of complex anatomical structures.ConclusionThe use of high-fidelity 3D scanning technology provides a promising alternative to traditional dissection by offering an accessible, sustainable, and detailed representation of spatial relationships in the human body. This approach enhances medical education and clinical practice, bridging the gap between theoretical knowledge and practical application.